Government Turnover in Parliamentary Democracies - Daniel Diermeier; Antonio Merlo (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
In this paper we consider a dynamic model of government formation and termination in parliamentary democracies. Our analysis accounts for the following observed phenomena: (1) Cabinet reshuffles; (2) Cabinet replacements; (3) Early elections; (4) Surplus governments; (5) Minority governments; (6) The relative instability of minority governments.
Keywords: D72; H19; C73; 330; government stability; minority coalitions; surplus coalitions